OX40+ T lymphocytes and IFN-γ are associated with American tegumentary leishmaniasis pathogenesis Linfócitos T OX40+ e IFN-γ estão associados com a patogênese da leishmaniose tegumentar americana - Patrícia Luciana Batista Domingos; Agostinho Gonçalves Viana; Carlos Alberto de Carvalho Fraga; Paulo Rogério Ferreti Bonan (Sociedade Brasileira de Dermatologia, 2012)
BACKGROUND: Leishmaniases are zoonoses considered a public health problem, representing a complex group of diseases with a broad clinical spectrum and epidemiological diversity. Leishmaniasis is caused by several species of protozoa of the genus Leishmania. The evolution of the pathology and the resolution of the leishmaniasis are dependent mainly on the Leishmania species involved, although the cytokine profile plays an important role in the development of the immune response. OBJECTIVES: The purpose of our study was to evaluate the immune response of patients affected by lesions of cutaneous leishmaniasis by immunostaining of the OX40, CD20, IFN-γ and IL-4 proteins. METHODS: The tissue samples were collected from indolent skin ulcers confirmed as cutaneous leishmaniasis of 41 patients aged between six and 90 years. The lesions were submitted to OX40, CD20, INF-γ and IL-4 immunolabeling. RESULTS: We observed a statistically significant higher expression of IFN-γ compared with IL-4 (p=0.009). Besides, OX40 had higher expression when compared with CD20 (p<0.001). CONCLUSION: The present study indicates that the immune response in lesions of cutaneous leishmaniasis is associated with a healing process, which can be explained by the higher expression of IFN-γ when compared with IL4 protein levels. FUNDAMENTOS: As leishmanioses são zoonoses consideradas um problema de saúde pública, representando um grupo de doenças complexas, com uma diversidade de amplo espectro clínico e epidemiológico. A leishmaniose é uma doença causada por várias espécies de protozoários do gênero Leishmania spp. A evolução da patologia e a resolução da leishmaniose são dependentes principalmente da espécie de Leishmania envolvida; embora o perfil das citocinas tenha um importante papel no desenvolvimento da resposta imune. OBJETIVOS: Proporcionar mais conhecimentos sobre os eventos inflamatórios na leishmaniose tegumentar através da avaliação da imunoexpressão de OX40, CD20, IFN-γ e IL-4. MÉTODOS: Foram coletadas amostras de tecido de 41 pacientes, com idade variando entre 6 a 90 anos, com úlceras indolentes na pele confirmados através de exames de diagnóstico como leishmaniose tegumentar. As lesões foram submetidas a imunomarcação das proteínas OX40, CD20, IFN-γ e IL-4. RESULTADOS: Observamos uma maior expressão de IFN-γ em comparação com IL-4, com diferenças estatisticamente significativa (p = 0,009). Além disso, OX40 tinha maior expressão quando comparada com IL-4 (p <0,001). CONCLUSÃO: O presente estudo indica que a resposta imune nas lesões de LTA está associada a um processo de cura, que pode ser explicado pela maior expressão de IFN-γ quando comparadas com os níveis de IL-4.